Truly United in Diversity: The European Union Thriving in Crisis? An Interview Study on Problem-Solving Behaviour in the European Union During the Ukraine Crisis - Cotton,Carl (2023)
The European Union (EU) has faced numerous severe crises during the 21st century. Rather than standing united and finding joint solutions, the intergovernmental negotiations have often revolved around furthering member state preferences, and maximising individual outcomes. Surprisingly, when Russia invaded Ukraine, in the spring of 2022, the EU managed to field a relatively successful and united response. This study takes aim at describing how and explaining why Problem-Solving behaviour occurred in these negotiations. Using a qualitative case study approach, and having collected data by interviewing civil servants representing Sweden in the EU-machinery, this study tests established negotiation theory and broadens our understanding of how external factors can affect the internal EU negotiations. The main finding is that when in a crisis context, for example when an External Threat is present, established behavioural tendencies are foregone due to an overriding mechanism. Problem-Solving behaviour can therefore take place, even though the negotiating context should favour Bargaining behaviour. This has clear implications for the decision-making process of the EU during a crisis context, and the EU as a global foreign policy entity. The study suggests that further research must be conducted within the field of crisis negotiations, in order to clearly understand how EU actors behave when facing a crisis.
Keywords: European Union; Negotiations; Crisis; Problem-Solving; Semi-Structured Interviews.